Accuracy test of laser tracker under condition of air turbulence - Kwiecień, Janusz (International Conference “Environmental Engineering”, 2017)
Laser tracking for interior industrial metrology is discussed. In this work, the effects of air turbulence on the angle of laser wave propagation is analyzed in the absence of the effects associated with other meteorological parameters (pressure, humidity) and particulate pollutants (dust, smoke). This analysis establishes the effectiveness of laser tracking under turbulent air conditions and quantification of deviations in the angular and linear accuracy from those provided by the manufacturer. An experimental setup and associated measurement method to determine the turbulence structure coefficient are described. It was found that turbulent air conditions resulted in a radical decrease in measurement accuracy. The reduction in accuracy was evidenced by a decrease in power and an increase in standard deviation of the laser beam, as well as a decline in the angle and distance measurement precision. The experimental measurements show a high correlation to predicted values.